2006 American Control Conference 2006
DOI: 10.1109/acc.2006.1657356
|View full text |Cite
|
Sign up to set email alerts
|

A novel Q-modification term for adaptive control

Abstract: A novel modification term is suggested for use in adaptive control. The development is of use in any setting in which uncertainty is linearly parameterized. The modification uses state and control time histories. The effect is justified through stability analysis, and illustrated on a dynamic model for wing rock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 12 publications
0
36
0
Order By: Relevance
“…To address this problem, the authors of [1][2][3][4][5][6][7][8] present modifications to adaptive update laws. In particular, the work in [1][2][3] uses filtered versions of the control input and state; [4][5][6] uses a moving time window of the system uncertainty; and [7,8] uses recorded and instantaneous data concurrently.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…To address this problem, the authors of [1][2][3][4][5][6][7][8] present modifications to adaptive update laws. In particular, the work in [1][2][3] uses filtered versions of the control input and state; [4][5][6] uses a moving time window of the system uncertainty; and [7,8] uses recorded and instantaneous data concurrently.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the work in [1][2][3] uses filtered versions of the control input and state; [4][5][6] uses a moving time window of the system uncertainty; and [7,8] uses recorded and instantaneous data concurrently. In contrast to these approaches, the authors of [9][10][11] present an approach called artificial basis functions that adds modification terms not only to the update law, but also to the adaptive controller and show that the system error can be suppressed during the transient system response.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be mentioned that there are other recently developed modifications to adaptive control such as the adaptive loop recovery method, 8 Kalman filter modification, 9 and Q-modification. 10 In the context of verifiable adaptive control, the optimal control modification exhibits an interesting property. Using a singular perturbation argument for fast adaptation, it can be shown that the asymptotic solution of the adaptive law for a linear uncertain system actually tends to a LTI model.…”
Section: Introductionmentioning
confidence: 99%